STUDY OF WET KINETICS GRINDING AND APPLICATION OF SURFACE-ACTIVE AGENTS (SURFACTANTS) (CAHIERS MAGELLANES-NS, 2024)
This paper is devoted to the study of grinding kinetics and the use of surfactants in the grinding process. Wet grinding, as a key technology in the mining, metallurgy and construction industries, demonstrates advantages over dry grinding, in particular, by reducing the strength of materials and improving grinding conditions due to the interaction of particles with a liquid medium.The study emphasizes the importance of choosing adequate technologies and additives to improve productivity and quality of the final product. The results of the work open up prospects for further research aimed at creating more efficient grinding technologies that contribute to the sustainable development of various production processes.